The development of an integrative proficiency test in English for first year high school students - Delmo, Zennia Marcella 1948- (1980)
This study was designed to measure the global proficiency in English of first year high school students through the integrative test. The test was given to 184 first year high school students of the Dingle Agricultural and Technical College at the end of the 1st semester of the school year 1979-1980. Based on the item analysis, the items were either retained, revised or discarded. Of the 206 numbered items, 160 items were retained. The item analysis also revealed that the lecturette test (missing words part) and the reading comprehension test had the highest percentage. Findings further indicate that the examinees found difficulty in answering questions eliciting interpretative responses, difficulty in distinguishing a faulty sentence from the grammatically correct ones, and their listening and writing skills were the least developed.
Appendices: [48] leaves
Thesis (M.Ed.)--University of the Philippines, Quezon City
Typescript.
Vita
m
Keywords: English language -- Examinations; English language -- Study and teaching (Secondary).